Studi Analisis Hadis Tsaqalain dalam Al-Kutub Al-Sittah - Umam, Khaerul Umam (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2025)
In contemporary times, conflicts frequently arise from differing interpretations of sacred texts, particularly the ḥadīth. Within the discipline of ḥadīth studies, the most contentious and vulnerable area lies in the dimension of understanding (fahm). This is unsurprising, given that ḥadīth—although rooted in divine revelation—are transmitted through human narrators, which opens interpretative space. One of the frequently debated traditions is the Prophet’s command to adhere to the Ahl al-Bayt. This study seeks to critically examine both the authenticity and the interpretation of the ḥadīth that mentions the Prophet’s two legacies (al-thaqalayn), namely the Qur’ān and the Ahl al-Bayt, particularly the narration transmitted by Zayd ibn Arqam. Employing a qualitative methodology, the research applies the methods of takhrīj al-ḥadīth, naqd al-sanad, naqd al-matn, and fiqh al-ḥadīth, supported by relevant classical and contemporary literature and peer-reviewed journal articles. The findings indicate that the narration of Zayd ibn Arqam is ṣaḥīḥ in terms of both its chain of transmission (sanad) and its content (matn). However, the understanding held by the salaf al-ṣāliḥ implies that the instruction to follow the Ahl al-Bayt is primarily intended to ensure the protection of their rights, while ultimate guidance remains the exclusive role of the Qur’ān. Therefore, in a contemporary context, it would be inaccurate to assert that the Ahl al-Bayt are equivalent to the Qur’ān as dual sources of authoritative guidance or inheritance of the Prophet.